PEMIDANAAN PENGURUS KOPERASI DALAM TINDAK PIDANA PENGGELAPAN SIMPANAN BERJANGKA (ANALISA PUTUSANNOMOR 76 /PID.B / 2014/ PN.MLG) - Samsul Aripin Silitonga; Alvi Syahrin; Muhammad Hamdan; Edi Yunara (USU LAW JOURNAL, 2018)
ABSTRACT     This thesis is entitled Criminal Cooperative Management In the Fraud Crime Time Deposit (Analysis of Decision Number 76 /Pid.B / 2014/ PN.Mlg). To answer the problem is done research using normative legal research, Using secondary data in the form of primary, secondary and tertiary legal material with legal approach method in answer formulation of problem about how arrangement about saving by saving and loan cooperative according to legislation about cooperative, how the criminal liability of cooperative management in criminal act of embezzlement of time deposit, How the judge's judgment in dropping the decree against the actions of the cooperative management commits a criminal act of embezzling the appropriate time deposits Analysis of Decision Number 76 /Pid.B / 2014/ PN.Mlg. The results showed that the judge in the imposition of criminal is based on the consideration of things that incriminate and relieve the criminal and criminal liabilities of futures imprisonment by the cooperative management is an action threatened with Article 374 of the Criminal Code because the management of the cooperative commits a crime by using the position as a board of cooperatives, able Responsible and no excuses of forgiveness. Judges in the imposition of criminal does not apply the criminal provisions contained in the Act to the fullest. Through this research, it is suggested that supervision and training of cooperative management as a form of prevention of abuse of authority carried out by cooperative management in order to conduct business activities in collecting the term saving funds implemented by the Cooperative Board in accordance with the provisions of the Law. The need for criminal imposition to the cooperative management by applying the criminal provisions contained in the Law to the maximum and the need for changes to Law No. 25 of 1992 on Cooperatives that regulate the criminal liability of cooperatives   Keywords: Time Deposit, Crime, Legal Consideration